STRATEGI PERBANKAN SYARIAH TERHADAP AKAD MUDHARABAH BERMASALAH PERMATA BANK SYARIAH DR. SUTOMO SURABAYA - ahmad kurniawan; warsidi warsidi (Universitas Muhammadiyah Surabaya, 2019)
ABSTRACTFinancing is a large part of Islamic bank assets that must be maintained in quality so that Islamic banks can carry out their functions properly. A common problem that arises is the existence of problematic financing that can continue to become a stagnant financing and cause financial health of the bank to be disrupted. The solution from National Sharia Board of Indonesian Ulema Council related to disputes in the contract is limited to 2 settlement efforts, namely deliberation, and settlement of disputes through the Sharia Arbitration Board, while the facts in the field indicate that the second solution is not widely implemented, and the form of deliberate deliberation makes each Islamic Financial Institutions carry out deliberations accordingly with their respective policies. Based on this, the research was carried out based on 2 legal issues, including legal vacancies, and the existence of multiple interpretations of each Islamic bank in running musyarah to handle troubled financing, one of which included PermataBank Syariah. From the legal issue, the formulation of the problem in this study was formed, namely: 1) how to finance the mudharabah contract at PermataBank Syariah; 2) how the Syariah Syariah Bank's strategy in handling troubled financing in mudharabah contracts. The method used in this study is sociological research with qualitative descriptive analysis because the research was carried out on direct conditions in the field. This qualitative descriptive is used to get data that is deep and meaningful. Mudharabah contract financing at PermataBank Syariah consists of 4 main stages, namely 1) prospective mudharib submits a request for financing; 2) if the requirements are complete, the bank will verify the data; 3) the bank surveys the field; 4) filling out the form and signing the contract by the prospective mudharib who passes verification. Efforts made by Permatabank Syariah KCS. Dr. Sutomo Surabaya in dealing with financing with problematic mudharabah contracts is divided into two approaches, namely, first, the pre-customer approach, which focuses on the selection of prospective customers. Second, the post-customer approach, which is carried out after the funds are disbursed to customers. If the two strategies are unsuccessful, then restructuring is carried out for customers who experience problem financing (Non-Performing Financing).Keywords: Islamic Bank, Mudharabah Agreement, Problem Financing, Non-Performing Financing, Banking Strategy